Facilitating positive attitudes towards an innovative programme for baccalaureate nursing education: - O. Adejumo; M. Ganga-Limando (AOSIS, 2000)
A survey of nurse ward leaders understanding of, and their attitude to, community/ problem based learning (CPBL) approach adopted for the education of nursing students in the degree programme of the University of Natal in Durban (UND) was conducted. This was with a view to intervening, if necessary, to ensure positive understanding and attitude among the nurse leaders towards the non-traditional CPBL of UND nursing students. It was hypothesised that focused discussions, between facilitators and nurse ward leaders, aimed at providing information and explanation about the advantages of changing from traditional to non-traditional educational programmes in nursing would enhance positive attitude towards the students and their education programme. Using a questionnaire developed for this study, quantitative and qualitative data were twice collected at intervals of 5-6 months from 54 nurse ward leaders who interacted with the CPBL students in 27 wards of 2 provincial hospitals. The data, collected in the early part of the students' deployment and at 5-6 months after included information about the participants understanding of CPBL; their rating of CPBL students in terms of expected knowledge and practice; and their attitude towards CPBL nursing students in clinical settings. Contact sessions were held with the participants in between the measures for a discussion about the CPBL programme and the expectations of the learners. Analysis of the pre and post measures showed more favourable attitude, improved understanding, and tolerance towards the students by the nurse ward leaders in the post-measures than in the pre-measures. The writers concluded that if students in this type of programme must experience satisfaction with less intimidation, implementers of CPBL programmes in nursing should relentlessly involve the qualified nurses and other professionals working with the students in informative discussions about the purpose and the process of learning in such programmes.